The poetic vision of the world in Zakłady holenderskie by Radosław Jurczak - Akram, Sara (Papers in Linguistics, 2025)
The aim of the article is to provide analysis of selected works from the book of poetry entitled Zakłady holenderskie by Radosław Jurczak, which raise the issue of technological development – particularly its impact on the world and humans. The interpretations are based on the semiotic-anthropological concept of style developed by Jerzy Bartmiński and Stanisława Niebrzegowska-Bartmińska, and the discussed values of style are: the way the poetic world exists in the collection, the adopted point of view and the image of the world correlated with it. The poetic world created in the volume is potential – it is a vision of the future based on scientific knowledge. One of the most significant conclusions which can be drawn is that this world is not anthropocentric – humans coexist in it with technological beings, and speech is no longer their distinctive feature. The speaking subject is rarely revealed in the selected poems in the form of the first person singular. Address-like phrases, enumerations and the parallel structure of the poems are frequently used techniques, which leads to introducing a new semantic quality with each reiteration.